Study on structure, surface morphology, electrical and magnetic properties in monovalent doped Pr0.75Na0.25Mn1-xCrxO3 AND Nd0.75Na0.25Mn1-yCryO3 of magnetic ceramics - Zawawi, Rabiatul Adawiyah (2021)
In perovskite manganites, Mn site substitution of Cr ion have attract great interest to suppress CO and induce phase transition. However most of study show inconsistent result regarding to the crystalline phase, surface morphology and magnetic properties as well as electrical properties study. Thus, two series of charge-ordered compound Pr0.75Na0.25Mn1-xCrxO3 (0≤x≤0.04) and Nd0.75Na0.25Mn1-yCryO3 (0≤y≤0.05) manganites have been synthesized using solid-state reaction method and the crystalline phase, surface morphology and magnetic properties as well as electrical properties were reported. Cr3+ have been chosen in this study due the electronic configuration which similar to Mn4+ where it is possibly involved in double-exchange mechanism. X-ray diffraction analysis revealed the crystalline phase of all samples consists of essentially single phase and crystallized in an orthorhombic structure. The Cr doping were influence the lattice parameters and the unit cell volume, V whereas the values of V was observed to be decreased for both manganites series. Scanning electron microscope images of both compounds showed the changes of surface morphology for all samples when Cr was doped. AC susceptibility and DC electrical resistivity measurement for both parent compounds (x = 0 and y = 0) showed paramagnetic-insulator down to lower temperature. Interestingly, increasing of Cr for Pr0.75Na0.25Mn1-xCrxO3 compound showed ferromagnetic-metallic (FMM) transition for x = 0.02 and x = 0.04 samples. Metal-insulator transition temperature, TMI were found to be TMI~120 K and TMI~122 K. Meanwhile for AC susceptibility measurement with Curie temperature, TC increases from 132 K to 141 K respectively and undergoes the transition paramagnetic to ferromagnetic state. While, the Nd0.75Na0.25Mn1-yCryO3 showed antiferromagnetic-insulator for y = 0, y = 0.02 and y = 0.05. Thus, the effect of Cr substitution on both manganites series showed significant results on crystalline phase, surface morphology and magnetic as well as electrical properties.